Avaliação de marcadores hemostáticos e pró-inflamatório na doença arterial coronariana - Adriano Basques Fernandes (2007)
Cardiovascular diseases constitute the main cause of death in worldwide justifying a number of investigations on this matter. The present study aimed to investigate the association between hemostatic parameters and reactive C protein (CRP), and the coronary artery disease (CAD) severity in 123 patients submitted to coronary angiography scored in three groups: a) normal angiographically (AnN,n=35; b) withmild/moderate atheromatosis (MA, n=31) and c) with severe atheromatosis (SA, n=57). The last group was divided into subgroups according to the number of affected vessels by the atherosclerotic process. Hemostatic parameters have included assessment of plasma levels of D dimmer (D-DI), plasminogen activator inhibitor type 1 (PAI-1), thrombin activatable fibrinolysis inhibitor (TAFI) and thrombomodulin (TM). CRP was also assessed as a marker of inflammatoryprocess. Analysis and interpretation of the results allowed concluding that the fibrinolytic system showed to be deficient in patients from the group with severe atheromatosis considering the levels significantly higher of PAI-1(p<0.001) in this group comparing to other patients groups. This fact indicates a parallelism between the levels of this inhibitor and the degree of stenosis in the arteries, although thenumber of affected vessels did not influence the results. Concerning to the other parameters assessed, none of them showed levels significantly elevated as the atherosclerotic disease become more severe, except the CRP, whose results showed to be higher in both groups with mild/moderate and severe atheromatosis in comparison to the angiographically normal group. The present study providesevidence that confirm previous findings related to the hypofibrinolytic state, as well as the involvement of inflammatory process in atherosclerotic diseases. However, the number of affected vessels, an unexplored variable so far, seemed not to contribute for elevating plasma levels of the assessed markers.